Chinese Medical Teams: Knowledge Transfer in Ethiopia and Malawi - Allison Grande; Sara Fischer; James Sayre (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2020)
This policy brief offers an in-depth analysis of Chinese Medical Teams (CMTs) and their work in Ethiopia and Malawi. What do CMTs offer to African health systems and what can be done to maximize their impact? Read along with Grande, Fischer, and Sayre to see what recommendations they have to improve CMTs' role within the healthcare system in Ethiopia and Malawi - and which lessons can also apply to other African nations.
Keywords: 330